Unique Features of Pancreatic-Resident Regulatory T Cells in Autoimmune Type 1 Diabetes - Lu, Jingli; Zhang, Chaoqi; Li, Lifeng; Xue, Wenhua; Zhang, Chengliang; Zhang, Xiaojian (Frontiers in Immunology, 2017)
Recent progress in regulatory T cells (Tregs) biology emphasizes the importance of understanding tissue-resident Tregs in response to tissue-specific environment. Now, emerging evidence suggests that pancreatic-resident forkhead box P3 (Foxp3)+ Tregs have distinguishable effects on the suppression of over-exuberant immune responses in autoimmune type 1 diabetes (T1D). Thus, there is growing interest in elucidating the role of pancreatic-resident Tregs that function and evolve in the local environment. In this review, we discuss the phenotype and function of Tregs residing in pancreatic tissues and pancreatic lymph nodes (PLNs), with emphasis on the unique subpopulations of Tregs that control the disease progression in the context of T1D. Specifically, we discuss known and possible modulators that influence the survival, migration and maintenance of pancreatic Tregs.